Diagnosis of Giardia infections by PCR-based methods in children of an endemic area - David, E. B. [UNESP]; Coradi, S. T.; Oliveira-Sequeira, T. C. G. [UNESP]; Ribolla, P. E. M. [UNESP]; Katagiri, S. [UNESP]; Guimaraes, S. [UNESP] (Universidade Estadual Paulista (Unesp), Centro de Estudos de Venenos e Animais Peçonhentos (CEVAP), 2011)
The present study was designed to estimate the prevalence of Giardia infection in preschool- and school-aged children living in an endemic area. Fecal samples from 573 children were processed by zinc sulfate centrifugal flotation, centrifugal sedimentation (using a commercial device for fecal concentration - TF-Test kit (R)) and polymerase chain reaction (PCR)-based methods. of the stool samples assessed, 277 (48.3%) were positive for intestinal parasites and/or commensal protozoa. Centrifugal flotation presented the highest diagnostic sensitivity for Giardia infections. The kappa index revealed that both coproparasitological techniques closely agreed on the Giardia diagnosis (86%) versus satisfactory (72%) and poor (35%) concordances for commensal protozoan and helminth infections, respectively. Concerning Giardia molecular diagnosis, from the 71 microscopy-positive samples, specific amplification of gdh and tpi fragments was noted in 68 (95.7%) and 64 (90%) samples, respectively. Amplification of gdh and tpi genes was observed, respectively, in 95.7% and 90% of microscopy-positive Giardia samples. For 144 microscopy-negative samples, gdh and tpi gene amplification products were obtained from 8.3% and 35.9% samples, respectively. The agreement between these genes was about 40%. The centrifuge-flotation based method was the most suitable means of Giardia diagnosis assessed in the present study by combining accuracy and low cost.
Keywords: Giardia duodenalis; children; diagnosis; PCR